Pengaruh Kualitas Layanan, Kepuasan Pelanggan, Dan Loyalitas Pelanggan Terhadap Niat Beli Ulang Pada Marketplace - Anisa Widiastuti; Anak Agung Ketut Diatmika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The large number of marketplace companies in Indonesia means that the level of competition between companies is increasing. Therefore, companies need to improve factors that can attract customers to repurchase intention. In today's business world, increasing repurchase intention strategies is a necessity, which can be achieved through improving service quality, customer satisfaction and customer loyalty. The aim of this research is to analyze the influence of service quality, customer satisfaction and customer loyalty on repurchase intentions in the marketplace, namely Tokopedia, in the Tangerang Regency area. This research uses a descriptive causality design with a quantitative method approach and uses purposive sampling techniques. Data was collected from 150 Tokopedia user respondents. Data analysis uses Partial Least Square-Structural Equation Modeling (PLS-SEM). Research findings reveal that service quality has a positive effect on customer satisfaction and customer loyalty. Furthermore, customer satisfaction has a positive effect on customer loyalty. Then, customer satisfaction has a positive effect on mediating the relationship between service quality and customer loyalty. And customer loyalty has a positive effect on repurchase intentions. Apart from that, perceived price can increase repurchase intentions. The contribution of this research provides insight into marketplaces in developing their business, as well as being able to plan and implement marketing strategies to create good service quality and positive assessments, in order to create repurchase intentions for products on marketplace.